GOVERNMENT REGULATION OF BUSINESS: ITS GROWTH, IMPACT AND FUTURE - MacAvoy, Paul W.; Tella, D M (Journal of Economic Literature, 1980)
Five papers explore the effects of regulation, the causes and consequences of its dramatic growth in the United States, and the prospects for deregulation. Specific topics include the impact of public utilities and transportation regulation on prices, output, investment, health and safety regulation, and environmental regulation; the indirect effects of regulation on competition (e.g., on the cost of new capacity and competitive positions of firms); the causes and consequences of major shifts in business-government relationships; conceptual and practical problems in measuring the costs of regulation; and an analysis of the legislative deregulation of the airline industry, with projections for deregulation in the railroad and trucking industries.